Meningkatkan Pengalaman Kuliner Online dengan Desain Website F&B yang Menarik - Andini, Mirna Ria; Andra Yusaldi Putra (LPPM Politeknik Aceh Selatan, 2024)
In the era of digital technology development, this research explains the process of designing websites using Html, Css, Javascript, and APIs. An attractive website has the potential to enhance the reputation of an individual or business and attract the attention of users. The waterfall development method was chosen to build the website. Performance evaluation is done using Gitsofspeed as a tool for measuring site speed and efficiency. The hope is to successfully address existing sales issues and increase positive impact, while stimulating consumer desire. Using technological advancements, an attractive website is able to provide information about food and beverages in a way that appeals to users